Transmission through muscle tissue shapes polarization signals during cuttlefish courtship - Arata Nakayama; Ryosuke Ohnuki; Shinya Yoshioka; Nobuhiro Ogawa; Toshihiko Kushihiki; Shunsuke Momoi; Noriyosi Sato; Tomohiko Kawamura; Yoko Iwata (Proceedings of the National Academy of Sciences, 2026)
Flamboyant sexual ornaments serve as conspicuous visual signals optimized to the visual receptors and perception of potential mates. While numerous studies have explored the mechanisms and functions of body coloration as a sexual signal, the role of another essential property of light—polarization—remains largely unexplored. Specifically, the question of whether and how polarization signals achieve high conspicuousness under sexual selection, including their visibility and associated behavioral and morphological adaptations, has yet to be thoroughly investigated. Here, we identified a strikingly conspicuous polarization signal used specifically during courtship in the cuttlefish Doratosepion andreanum and investigated the underlying optical mechanism. The signal consists of a pattern of adjacent horizontally and vertically polarized areas, optimizing signal detectability for cephalopod polarization vision. This pattern is generated by reflective cells called iridophores and transparent muscle: light becomes horizontally polarized when reflected by iridophores, and its angle of polarization is then rotated to vertical when transmitted through a birefringent muscle layer. Our findings show the significant contribution of polarization of light to animal communication and reveal that polarization signals—like colorful sexual ornaments—can achieve high conspicuousness through fundamentally different optical mechanisms.